FITRAH DALAM PERSPEKTIF AL-QURAN DAN IMPLIKASINYA TERHADAP PENDIDIKAN ISLAM - Rohmadi . (MUADDIB Jurnal Kependidikan dan Keislaman, 2016)
Islam does not depart from the empiricism, nativism, and convergence theory. Islam, however, through the interpretation of Koran and Hadith offer human development theory, that man in the beginning is to have the nature of the Islamic religion, man has divinity as embodied in the names of God in Islam. Humans also have the physical, brain, spiritual sense and other, which at this stage greatly determined by external influence both positive and negative, and its dialogic with the internal potential in man, which then to pick and choose in response to the external influences. Education is a means to maintain a religious nature brought, and also develop the potential both physical and spiritual sense.The potential to be developed into marifat to the Almighty God, as a servant and caliph on the earth that believe and fear to Allah, to everything noble and a blessing for the entire universe. Therefore, an attempt to influence the physical and spiritual human beings through education is possible and can play a positive role to direct the development of a person to the path of truth. This can be done by parents, communities, and teachers because without effort through the good education of the parents, the children will fail into error. Besides, parents are also part of society and educational intitutions who can be categorized as an environment for children who have a significant effect on their education.